Clinical outcomes of early remdesivir administration in hospitalized patients at high risk for severe COVID-19 during the Omicron wave - Yeon Ju La; Won Sup Oh; Changhyup Kim; Myoung-nam Lim; Yong Duk Jeon (BMC Infectious Diseases)
Abstract Background Early remdesivir administration in high-risk patients with coronavirus disease 2019 (COVID-19) is known to be effective in preventing the progression to severe disease. However, the effect of early remdesivir administration on Omicron variants, which are known to have decreased severity, remains unclear. Methods This study aimed to analyze the effects of early remdesivir administration during the Omicron wave in hospitalized patients. Electronic medical records of hospitalized patients with confirmed COVID-19 between February 2022 and February 2023 were reviewed. We included patients aged ≥ 18 years who had symptom onset within 7 days and had at least one risk factor for disease progression at the time of diagnosis. We compared the clinical outcomes between the early remdesivir administration group and the group not administered early remdesivir. The primary outcome was all-cause mortality within 28 days and the secondary outcome was the need for oxygen supplementation within 28 days. Multivariable analysis was conducted to assess risk factors for all-cause mortality and the need for oxygen supplementation. Results A total of 286 patients were enrolled, including 88 in the early remdesivir administration group and 198 in the control group. Clinical outcomes, including all-cause mortality (3.4% vs. 6.1%, P = 0.556) and need for oxygen supplementation (15.9% vs. 14.6%, P = 0.783) within 28 days, were not significantly different between the two groups. Age (HR, 1.061; 95% CI: 1.002, 1.124; P = 0.043), BMI (HR, 0.849; 95% CI: 0.725, 0.994; P = 0.041), and malignancy (HR, 4.619; 95% CI: 1.618, 13.189; P = 0.004) were identified as independent factors associated with all-cause mortality. Additionally, BMI (OR, 0.908; 95% CI, 0.824, 1.000; P = 0.049) and vaccination with more than three doses (OR, 0.412; 95% CI, 0.202, 0.839; P = 0.015) were independent factors associated with the need for oxygen supply. Early remdesivir administration was not significantly associated with all-cause mortality (HR, 0.393; 95% CI: 0.109, 1.417; P = 0.154) or the need for oxygen supplementation (OR, 0.823; 95% CI: 0.389, 1.740; P = 0.610). Conclusions In our study, early remdesivir administration was not associated with preventing progression to severe disease when used as previously indicated during the Omicron wave. Considering the decline in the severity of the Omicron variant and the increased vaccination rate reported in previous studies, further studies are needed to establish new indications for the use of early remdesivir in the Omicron variant.